2014
DOI: 10.1126/science.1258268
|View full text |Cite
|
Sign up to set email alerts
|

Recent introduction of a chytrid fungus endangers Western Palearctic salamanders

Abstract: Emerging infectious diseases are reducing biodiversity on a global scale. Recently, the emergence of the chytrid fungus Batrachochytrium salamandrivorans resulted in rapid declines in populations of European fire salamanders. Here, we screened more than 5000 amphibians from across four continents and combined experimental assessment of pathogenicity with phylogenetic methods to estimate the threat that this infection poses to amphibian diversity. Results show that B. salamandrivorans is restricted to, but high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
706
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(767 citation statements)
references
References 30 publications
(12 reference statements)
15
706
5
4
Order By: Relevance
“…Similarly, we have gained important insights into the European emergence of another chytrid fungus, Batrachochytrium salamandrivorans (Bsal) [3]. Unfortunately, the development of field interventions for disease management has lagged far behind and managing amphibian health in nature remains a largely unexplored topic [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, we have gained important insights into the European emergence of another chytrid fungus, Batrachochytrium salamandrivorans (Bsal) [3]. Unfortunately, the development of field interventions for disease management has lagged far behind and managing amphibian health in nature remains a largely unexplored topic [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…via trade regulations, such as the recent establishment of restrictions on caudate amphibian trade in the USA in response to the emergence of B. salamandrivorans, https://federalregister.gov/a/2016-00452) are probably the most effective disease mitigation measure available [9,10]. The international movement of amphibians plays a continuing role in establishing and extending the distribution of amphibian-associated chytrids and other pathogens, but the control of chytridiomycosis and other purely wildlife diseases is largely overlooked in commercial trade [3,[11][12][13]. The World Organisation for Animal Health (OIE) is the international body that can regulate this, but even though its remit includes wildlife conservation it has a poor track record in doing so.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous experiments 6 suggested that the host-range of Bsal was limited to species of newts and salamanders, the authors found that a species of frog, Alytes obstetricans, could be infected by the fungus and transmit the disease to salamanders. Infection of alpine newts (Ichthyosaura alpestris) that share the forests with the salamanders alongside A. obstetricans then showed that the newts could develop chronic Bsal infections.…”
mentioning
confidence: 91%
“…Recently, a second Batrachochytrium species (B. salamandrivorans) of probable Asian origin has been identified causing catastrophic die offs in salamanders in the Netherlands (Martel et al 2013. Unlike Bd, the new pathogen seems to be restricted to urodele hosts (Martel et al 2014). However, Batrachochytrium species are not the only pathogens which infect amphibians.…”
Section: Introductionmentioning
confidence: 99%